Determination of fluquinconazole, pyrimethanil, and clofentezine residues in fruits by liquid chromatography with ultraviolet detection - Navickiene, Sandro [UNESP]; Ribeiro, Maria Lúcia [UNESP] (Oxford University Press (OUP), 2004)
A simple method was developed for the determination of fluquinconazole, pyrimethanil, and clofentezine in whole fruit; peel; and pulp of mango, apple, and papaya. These compounds were extracted from fruit samples with a mixture of ethyl acetate-n-hexane (1 + 1, v/v). An aliquot (2 mL) of the extract was evaporated to near dryness under a stream of nitrogen, and the residue was dissolved with 2 mL methanol. The analysis was performed by means of liquid chromatography with ultraviolet detection at 254 nm using a gradient solvent system. The method was validated with fortified fruit samples at concentration levels of 0.05, 0.10, 0.20, and 0.50 mg/kg. Average recoveries (4-8 replicates) ranged from 80 to 95% with relative standard deviations between 3.5 and 12.7%. Detection limits ranged from 0.03 to 0.05 mg/kg for fruit pulp and 0.03 mg/kg for whole fruit. The quantitation limits ranged from 0.05 to 0.10 mg/kg for fruit pulp and 0.05 mg/kg for whole fruit. The analytical method was applied to fruit samples obtained from local markets.